Visual analysis of research progress and trend on hairy roots - Zheng, Yu-Ping (Frontiers in Plant Science, 2025)
Hairy root is a special form of root tissue, which is induced by Rhizobium rhizogenes and could mediate genetic transformation after the infection of explants. They have attracted attentions because of their advantages of fast growth rate, convenient culture, stable genetic properties and strong synthesis ability of secondary metabolites. With bibliometrics, this study employed CiteSpace and VOSvivewer softwares to analyze the publications on hairy roots researches from 2009 to 2024 based on WOS database. The subject distribution, countries, institutions and personnel, research hotspots and research trends of hairy roots were discussed and analyzed. The results revealed a consistent increase in publications on hairy root with America, China and India as the main countries. The institutions were mainly universities and the Chinese Academy of Sciences was a major contributor to this topic and had close cooperation with other institutions. The researches of hairy roots mainly focused on plant genetic transformation, secondary metabolism and gene molecular function analysis, and in environmental remediation. The application of hairy roots could be an important research hotspot in the future.